Gerakan Literasi Sekolah untuk Menguatkan Minat Literasi Siswa Kelas Internasional MTs Mu’allimin Muhammadiyah Yogyakarta - Purwaka, Adha Ridho (Fakultas Ilmu Pendidikan, 2026)
This study explores the implementation of the School Literacy Movement (GLS) policy as an effort to enhance reading and writing interest among international class students at MTs Mu’allimin Muhammadiyah Yogyakarta. Employing a qualitative descriptive method, data were gathered through interviews, observations, and documentation, then analyzed using an interactive model. The findings indicate that the implementation of GLS has been effectively carried out through consistent communication, sufficient human and material resources, supportive implementer disposition, and a well-structured bureaucratic system. Key supporting factors include structured coordination, access to digital literacy platforms, and institutional commitment. However, challenges remain in the form of limited supervision of student technology use and insufficient foreign language proficiency among some students. The study concludes that GLS, when adapted to the blended curriculum context, contributes significantly to fostering a sustainable literacy culture